2017
DOI: 10.1103/physrevb.95.155131
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport in disordered metals without quasiparticles: The Sachdev-Ye-Kitaev models and holography

Abstract: We compute the thermodynamic properties of the Sachdev-Ye-Kitaev (SYK) models of fermions with a conserved fermion number, Q. We extend a previously proposed Schwarzian effective action to include a phase field, and this describes the low temperature energy and Q fluctuations. We obtain higherdimensional generalizations of the SYK models which display disordered metallic states without quasiparticle excitations, and we deduce their thermoelectric transport coefficients. We also examine the corresponding proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

42
677
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(719 citation statements)
references
References 87 publications
42
677
0
Order By: Relevance
“…More evidence for the energy diffusion bound (D e /v 2 B ) was shown in holographic models that flow to AdS 2 ×R d fixed points in the infrared in [20] and in the Sachdev-Ye-Kitaev (SYK) models [21][22][23]. 4 However, it was shown that charge diffusion (D c /v 2 B ) may not have a universal lower bound in striped holographic matter [24] and in the SYK model [22]. When the higher derivative correction is added the energy diffusion (D e /v 2 B ) still can have a lower bound while the charge diffusion (D c /v 2 B ) may vanish depending on the higher derivative couplings [25].…”
Section: Jhep06(2017)030mentioning
confidence: 99%
See 2 more Smart Citations
“…More evidence for the energy diffusion bound (D e /v 2 B ) was shown in holographic models that flow to AdS 2 ×R d fixed points in the infrared in [20] and in the Sachdev-Ye-Kitaev (SYK) models [21][22][23]. 4 However, it was shown that charge diffusion (D c /v 2 B ) may not have a universal lower bound in striped holographic matter [24] and in the SYK model [22]. When the higher derivative correction is added the energy diffusion (D e /v 2 B ) still can have a lower bound while the charge diffusion (D c /v 2 B ) may vanish depending on the higher derivative couplings [25].…”
Section: Jhep06(2017)030mentioning
confidence: 99%
“…3 This idea was first tested at zero density in a class of holographic model with an scaling infrared geometry in [15,19], where concrete examples supporting the bound (1.8) with the butterfly velocity were provided. More evidence for the energy diffusion bound (D e /v 2 B ) was shown in holographic models that flow to AdS 2 ×R d fixed points in the infrared in [20] and in the Sachdev-Ye-Kitaev (SYK) models [21][22][23]. 4 However, it was shown that charge diffusion (D c /v 2 B ) may not have a universal lower bound in striped holographic matter [24] and in the SYK model [22].…”
Section: Jhep06(2017)030mentioning
confidence: 99%
See 1 more Smart Citation
“…Or, one can consider a Lorentz invariant higher-dimensional bosonic SYK [30]. For other generalizations, see [19,[50][51][52][53][54][55][56][57][58][59]. In addition, in the study of AdS 2 /CFT 1 one must regulate the bulk, introducing a dilaton and turning it into "nearly" AdS 2 .…”
Section: Jhep05(2017)092mentioning
confidence: 99%
“…As one notable example, Majorana-fermion zero modes [1,2] capture the essence of non-Abelian statistics and topological quantum computation [3,4], and correspondingly now form the centerpiece of a vibrant experimental effort [5][6][7][8][9][10][11][12][13][14][15][16]. More recently, randomly interacting Majorana fermions governed by the "Sachdev-YeKitaev (SYK) model" [17][18][19] were shown to exhibit sharp connections to chaos, quantum-information scrambling, and black holes-naturally igniting broad interdisciplinary activity (see, e.g., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). The goal of this Rapid Communication is to exploit hardware components of a Majorana-based topological quantum computer for a tabletop implementation of the SYK model, thus uniting these very different topics.…”
mentioning
confidence: 99%